Cognitive deficits in children with autism spectrum disorders: Toward an integrative approach combining social and non-social cognition - Hajri, Melek; Abbes, Zeineb; Yahia, Houda Ben; Jelili, Selima; Halayem, Soumeyya; Mrabet, Ali; Bouden, Asma (Frontiers in Psychiatry, 2022)
Autism spectrum disorder (ASD) is associated with neurocognitive impairment, including executive dysfunctioning and social cognition (SC) deficits. Cognitive remediation (CR) is a behavioral training-based intervention aiming to improve cognitive processes. Its first use in psychiatry interested patients with schizophrenia, in whom promising results have been shown. Integrated CR programs targeting both social and non-social cognition have demonstrated to be effective in improving both cognitive domains and functional outcomes. CR studies in children and adolescents with ASD are still new, those regarding CR approaches combining social and executive functioning remediation are scares. One study examining the efficacy of cognitive enhancement therapy (CET) for improving cognitive abilities in ADS adults, showed significant differential increases in neurocognitive function and large social-cognitive improvements. Therefore, taking into account the overlap between ASD and schizophrenia, and considering the close link between executive functions (EF) and SC, we suggest that integrative approach in ASD could result in better outcomes. The present perspective aimed to highlight cognitive remediation (CR) programs contributions in ASD (especially in children and adolescents), and to discuss the value of combining social and non-social programs.